2011
DOI: 10.1074/jbc.m110.206433
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Nucleotide and Sugar 1-Phosphate Promiscuity of Nucleotidyltransferase RmlA via Directed Evolution

Abstract: Directed evolution is a valuable technique to improve enzyme activity in the absence of a priori structural knowledge, which can be typically enhanced via structure-guided strategies. In this study, a combination of both whole-gene error-prone polymerase chain reaction and site-saturation mutagenesis enabled the rapid identification of mutations that improved RmlA activity toward non-native substrates. These mutations have been shown to improve activities over 10-fold for several targeted substrates, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…Therefore, we prepared all five possible NDP-valienols and evaluated the substrate preference of VldE – whether or not it can process other NDP-valienols. GDP-, ADP-, and CDP-valienols were prepared from valienol 1-phosphate and their corresponding nucleotidyl triphosphates (GTP, ATP, or CTP), using VldB (Yang et al, 2011), whereas UDP- and dTDP-valienol were prepared from valienol 1-phosphate and UTP and dTTP, respectively, using RmlA-L89T, an engineered broad spectrum nucleotidyltransferase (Moretti et al, 2011), kindly provided by Prof. Jon Thorson at the University of Kentucky (Figures S2A and S2B). Although RmlA-L89T has been known to have relaxed substrate specificity towards various sugar phosphates (Moretti et al, 2011), the present study showed that RmlA-L89T is also able to process an unsaturated carbasugar phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we prepared all five possible NDP-valienols and evaluated the substrate preference of VldE – whether or not it can process other NDP-valienols. GDP-, ADP-, and CDP-valienols were prepared from valienol 1-phosphate and their corresponding nucleotidyl triphosphates (GTP, ATP, or CTP), using VldB (Yang et al, 2011), whereas UDP- and dTDP-valienol were prepared from valienol 1-phosphate and UTP and dTTP, respectively, using RmlA-L89T, an engineered broad spectrum nucleotidyltransferase (Moretti et al, 2011), kindly provided by Prof. Jon Thorson at the University of Kentucky (Figures S2A and S2B). Although RmlA-L89T has been known to have relaxed substrate specificity towards various sugar phosphates (Moretti et al, 2011), the present study showed that RmlA-L89T is also able to process an unsaturated carbasugar phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…Substitution with amino acid residues smaller than the original 97th (103rd in EcGlmU) Tyr residue of the ST0452 protein increased the GlcNAc-1-P UTase activities of both ST0452 and EcGlmU proteins. Similarly, in the bacterial sugar-1-P TTase enzyme, substitution with smaller amino acid residues expands the nucleoside triphosphate or sugar-1-P substrate specificity (12,13,14,15). Structure-based substitution mutants have been designed for expansion of the substrate specificity, primarily due to improvement in K m values (13).…”
Section: Discussionmentioning
confidence: 99%
“…A prevalent, pathogenic organism, S. pneumoniae has shown widespread clinical resistance to penicillin and chloramphenicol, as well as to synergistic treatments involving β-lactams and aminoglycosides. 5,6 Furthermore, they have been used to prepare sugar nucleotide analogues for enzymatic glycodiversification studies, [7][8][9] and used to prepare phosphonate 10 and carbacyclic 11 sugar nucleotide analogues that have been put forward as putative glycosyltransferase inhibitors. Cps2L (EC 2.7.7.24) is a bacterial thymidylyltransferase (nucleotidylyltransferase) cloned from S. pneumoniae that catalyses the first step in the biosynthesis of L-rhamnose (Scheme 1), 3 an essential constituent of the cell wall in many bacterial species.…”
Section: Introductionmentioning
confidence: 99%